The Strategies Employed by Ecowas in Promoting Democratic Government in Nigeria - Felix, Nikoro; Clark, V. E. (Universitas Indonesia Mandiri, 2026)
The study examined the strategies employed by ECOWAS in promoting democratic government in Nigeria. To achieve a specific objective and research question was derived to guide the study. The structural functionalist theory was used for the study. The historical research design was adopted for the study to help analyze the historical trend of past events to account for the present. Secondary data was collected for the study. The qualitative research method of data analysis that relies on positive literature was used to analyze the research questions. The study discovered that ECOWAS has strategies outlined for the achievement of democratic consolidation in Africa, with emphasis on Nigeria. It further established that ECOWAS is faced with the challenges of funding that inhibit the achievement of the strategies for democratic consolidation. It was recommended that the challenges of funding and implementation of ECOWAS treaties within West Africa and Nigeria can be addressed, with the involvement of independent donors and sponsors within Africa and the diaspora. The study affirmed the need for ECOWAS to design strategies that are amenable to change and flexible due to the dynamic nature of society that is continuously evolving.